2013
DOI: 10.1136/bmjopen-2013-004034
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory infections in preterm infants and subsequent asthma: a cohort study

Abstract: ObjectivesTo investigate whether gestational age modifies the association of airway infections that result in hospital admission during the first year after birth, with subsequent asthma risk after age 5 years.SettingHospital inpatients and a general population comparison group in Sweden followed for subsequent diagnoses in primary and secondary care.ParticipantsNational registers identified 42 334 children admitted to hospital for respiratory infection in their first year after birth during 1981–1995, individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…In this analysis the overlapping hazard ratios across the various gestational age categories suggests the relationship of early and recurrent ARI with increased risk of later respiratory hospitalisation and asthma is similar in preterm infants and late term infants. MONTGOMERY et al [27] conducted a similar analysis of a large Swedish population cohort. The authors did report effect modification with gestational age with the risk of subsequent asthma after 5 years, but only in those born at <28 weeks gestation and they did not explore recurrent ARI in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis the overlapping hazard ratios across the various gestational age categories suggests the relationship of early and recurrent ARI with increased risk of later respiratory hospitalisation and asthma is similar in preterm infants and late term infants. MONTGOMERY et al [27] conducted a similar analysis of a large Swedish population cohort. The authors did report effect modification with gestational age with the risk of subsequent asthma after 5 years, but only in those born at <28 weeks gestation and they did not explore recurrent ARI in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the majority of the data on the long-lasting impact of RSV have been based on studies of healthy term-born infants, limited studies have demonstrated increased risk of asthma [68], recurrent wheeze [34,69,70] and lung function impairments [66] in preterm children with a history of RSV-related hospitalisation during infancy. Early-life hospitalisation with RSV infection in preterm infants has been associated with more than twice the risk of ongoing respiratory morbidity, with wheezing rates ranging from 20.7 to 42.8%, 1–2 years following RSV-related hospitalisation compared to 4.1 to 23% following non-RSV related hospitalisation [43].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Early-life hospitalisation with RSV infection in preterm infants has been associated with more than twice the risk of ongoing respiratory morbidity, with wheezing rates ranging from 20.7 to 42.8%, 1–2 years following RSV-related hospitalisation compared to 4.1 to 23% following non-RSV related hospitalisation [43]. The risk of asthma, recurrent wheeze and long-lasting impairments in lung function following severe RSV-related respiratory illness during infancy is more pronounced among preterm infants with BPD [66,71] and those born at a lower gestational age [68]. Although most studies demonstrating persistent respiratory morbidity following RSV-related respiratory illness have focused on hospitalised infants, a single study has demonstrated persistent airway resistance at 1 year of age in preterm infants following mild RSV infection that did not require hospitalisation [72].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…A birth cohort from Sweden consisting of 42 334 children hospitalised for respiratory infections during their first year of life [112] was compared with 211 594 control subjects. It was found that experiencing a viral or bacterial respiratory infection at ,12 months old resulted in a 50% higher risk of asthma at 5 years of age; this increased risk of asthma persisted up to 16 years of age.…”
Section: Viral Respiratory Infectionsmentioning
confidence: 99%